1999
DOI: 10.1046/j.1440-1819.1999.00617.x
|View full text |Cite
|
Sign up to set email alerts
|

Cultural difference in recognition of facial emotional expression: Contrast between Japanese and American raters

Abstract: INTRODUCTIONRecently, the study of faces has become popular. These studies range from the investigation of beauty and attraction, 1 to the psychiatrically relevant topics of percentage changes of emotional expressions in depression and schizophrenia. 2 Cross-cultural issues have been addressed extensively, 3-6 while high technological approaches include the identification of brain structures responsible for registering fear or aggression. 7,8 In order to identify the most suitable paradigm for investigating ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 13 publications
1
31
0
Order By: Relevance
“…These findings are difficult to interpret given a lack of relevant literature. Although cross-cultural emotional recognition has been investigated (Ekman and Friesen, 1971; Schimmack, 1996; Shioiri et al, 1999), with results generally indicating greater accuracy among persons of similar racial and/or ethnic background (Elfenbein and Ambady, 2002), this body of research does not speak directly to the current study for two reasons. First, previous studies have emphasized the race/ethnicity of the observer, whereas we focused exclusively on the observed person (VH patient); the sample was insufficiently diverse to examine nurse-by-patient race interaction effects.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These findings are difficult to interpret given a lack of relevant literature. Although cross-cultural emotional recognition has been investigated (Ekman and Friesen, 1971; Schimmack, 1996; Shioiri et al, 1999), with results generally indicating greater accuracy among persons of similar racial and/or ethnic background (Elfenbein and Ambady, 2002), this body of research does not speak directly to the current study for two reasons. First, previous studies have emphasized the race/ethnicity of the observer, whereas we focused exclusively on the observed person (VH patient); the sample was insufficiently diverse to examine nurse-by-patient race interaction effects.…”
Section: Discussionmentioning
confidence: 97%
“…Cross-cultural recognition of emotional expressions has also received empirical attention (Ekman and Friesen, 1971; Schimmack, 1996; Shioiri et al, 1999). A meta-analysis indicated that individuals are more accurate in identifying the expressions of persons who share their racial/ethnic background (Elfenbein and Ambady, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…While results from early cross-cultural investigations of emotion perception support the presence of some level of cultural universality in emotion perception and production (Ekman et al, 1969; Ekman and Friesen, 1971; Izard, 1971), more recent results reveal cross-cultural differences in cognition and behavior (for review see Nisbett and Masuda, 2003), including the domain of emotion perception (e.g., Ekman et al, 1987; Matsumoto and Ekman, 1989; Biehl et al, 1997; Yrizarry et al, 1998; Nisbett et al, 2001; Matsumoto et al, 2002; Jack et al, 2012b). Prior experiments employing full-face and high-intensity expressions, have identified a gradient of cultural agreement that is greatest for positive emotions, such as happiness, and lowest for negative emotions, such as fear and anger (Ekman et al, 1987; Matsumoto, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…However, according to findings on cultural differences in emotion processing behavior: e.g. [33-35]; neural correlates: e.g., [16,18], we posited a significant impact of ethnic group on behavioral and neural responses that affects the amygdala: we hypothesized stronger amygdala activation in the female Asian sample as they were out-group to the ethnic group of posers presented (i.e., Caucasians). Considering previous results on the significant effect of duration of stay on emotion recognition performance [36] and amygdala activation in male immigrants [18], we also expected a significant association between duration of stay and behavioral performance and amygdala activation in Asian females.…”
Section: Introductionmentioning
confidence: 99%